Evidence for a Correlation of Melt Fragility Index With Topological Phases of Multicomponent Glasses - Chbeir, Ralph; Bauchy, Mathieu; Micoulaut, Matthieu; Boolchand, Punit (Frontiers in Materials, 2019)
Scores of glass compositions in the equimolar GexAsxSe100−2x ternary system are synthesized across the 0 < x < 26% range, and their homogeneity tracked by ex-situ Raman profiling. In synthesis, we alloyed the starting materials to homogenize until the variance, <Δ×>Ge, in Ge content “x,” across a 1.5-g sized batch composition of <0.01% was realized. We undertook Modulated-DSC, Raman scattering, and molar volume experiments as a function of composition. Trends in Tg(x) increase monotonically with x over the examined range, but the non-reversing enthalpy of relaxation at Tg, ΔHnr(x), displays a sharp square-well like reversibility window over the 9.5(2)% < x < 17.0(2)% range even in rejuvenated glasses. Trends in melt fragility index, m(x), established by measuring the T-dependence of the enthalpy relaxation time across Tg, show a Gaussian-like variation with m(x) < 20 in the 9.5(2)% < x < 17.0(2)% range, and m > 20 outside that range, thus establishing a fragility window. The close correlation between the variations of m(x) and ΔHnr(x) underscores that super-strong melts formed in the fragility window form Intermediate Phase (IP) glasses in the reversibility window, while fragile melts formed at non-IP compositions give rise to either flexible or stressed-rigid glasses. Molar volumes of glasses reveal a global reduction for IP glass compositions, thereby underscoring the compacted nature of the isostatically rigid networks formed in that phase. Evidence for specific dynamic features of the different phases is provided by molecular dynamics simulations, which indicate that the diffusivity is minuscule for x > 17% and increases substantially in the flexible phase. These results show that liquid dynamics and fragility encode glass topological phases in this ternary chalcogenide. The optimization of the glass-forming tendency for IP compositions, the stress-free nature of these networks, and the qualitative suppression of aging, are features that all point to their ideal nature. These ideas of IP glasses as ideal glasses are at variance with the notion that ideal glasses possess a low configurational entropy and form at Tg values that approach the Kauzmann temperature. IP networks display, adaptability, high glass-forming tendency, stress-free nature, and high configurational entropy of networks.